143 GOSH patient safety toolkit: development of a mobile application (App) to improve compliance with staff mandatory training. (December 2018) - Krashia, Y; Rios, C; Odufuwa-Bolger, S; Mohamedally, D; Conner, S; Sebire, NJ; Follett, R; Banaghan, M
Abstract : Background: The mandatory training of new staff includes the awareness of clinical guidelines to improve patient safety but compliance using traditional online methods may be poor due to the inability to access and complete training on mobile devices at a convenient time. Aim: The aim of this study was to create a mobile training app that would encourage staff participation in mandatory training using the 'Sepsis 6' guidelines in recognition of the increasing importance of early detection of sepsis to ensure a good patient outcome. Methods: We developed a cross-platform mobile application using the Ionic platform, HTML, CSS, and angular. Results: We demonstrate a working prototype of the 'Patient Safety Toolkit' app which displays interactive, menu-driven content, a video library and the ability to generate personal learning notes which can be stored and emailed. Initial testing demonstrated an acceptable user interface with a good usability of the entire functionality of linking personalised notes and information. The familiar mobile user interface design, with hierarchical menus and clean design, resulted in minimal instructional requirements and intuitive use by testers. Conclusion: It has been recognised that this app can be used widely across clinical specialties and further work is required to extend the functionality to include additional content, to track and record usage and progress and to develop quiz/gamification elements to generate leaderboards and departmental metrics.